Will Earth's next supercontinent assemble through the closure of the Pacific Ocean? - Huang, Chuan; Li, Zheng-Xiang; Zhang, Nan (OXFORD UNIV PRESS, 2022)
Earth's known supercontinents are believed to have formed in vastly different ways, with two endmembers being introversion and extroversion. The former involves the closure of the internal oceans formed during the break-up of the previous supercontinent, whereas the latter involves the closure of the previous external superocean. However, it is unclear what caused such diverging behavior of supercontinent cycles that involved first-order interaction between subducting tectonic plates and the mantle. Here we address this question through 4D geodynamic modeling using realistic tectonic set-ups. Our results show that the strength of the oceanic lithosphere plays a critical role in determining the assembly path of a supercontinent. We found that high oceanic lithospheric strength leads to introversion assembly, whereas lower strength leads to extroversion assembly. A theoretically estimated reduction in oceanic crustal thickness, and thus its strength, during Earth's secular cooling indicates that introversion was only possible for the Precambrian time when the oceanic lithosphere was stronger, thus predicting the assembling of the next supercontinent Amasia through the closure of the Pacific Ocean instead of the Indian-Atlantic oceans. Our work provides a new understanding of the secular evolution of plate tectonics and geodynamics as the Earth cooled.